Teknik dan media komunikasi kesehatan yang efektif dalam penyampaian informasi pencegahan dan vaksinasi COVID-19 pada remaja - Arif Nugroho Triutomo; Hasan Basri Borut (Poltekkes Kemenkes Yogyakarta, 2021)
Based on the survey results, the 17-30 year age group in carrying out the health protocol of washing their hands for 20 seconds with soap was only 66.0%, in contrast to the 46-60 year age group and > 60 years reaching > 80%. The young age group is also a group that is more confident that it is unlikely to be infected with the COVID-19 virus, reaching 20.2%, in contrast to the 31-45 year old group, which only 15.4% stated that it was very unlikely to be infected with the COVID-19 virus. The output target of this community service program is to increase and increase adolescent knowledge about how to prevent and vaccinate COVID-19 and to be able to disseminate information about prevention and vaccination of COVID-19. The method used in community service activities, especially youth at the Mantrijeron Ministry is the socialization method regarding the introduction of effective communication media in delivering information on COVID-19 Prevention and Vaccination to adolescents. The result of this community service is the BERANI Poster